Study of the Refraction Effects in Microwave Breast Imaging Using a Dry Setup - Godinho, Daniela M. (2020)
Medical Microwave Imaging (MWI) has been studied as a technique to aid breast cancer diagnosis. Several different prototypes have been proposed but most of them require the use of a coupling medium between the antennas and the breast, in order to reduce skin backscattering and avoid refraction effects. The use of dry setups has been addressed and recent publications show promising results. In this paper, we assess the importance of considering refraction effects in the image reconstruction algorithms. To this end, we consider a simplified homogeneous spherical model of the breast and analytically compute the propagating rays through the air-body interface. The comparison of results considering only direct ray propagation or refracted rays shows negligible impact on the accuracy of the images for moderately high permittivity media. Thus, we may avoid the computational burden of calculating the refracted rays in complex shapes.